The impacts of climate change and air pollution on children's education outcomes: Evidence from Vietnam - Hai-Anh H. Dang; Minh N. N. Do; Cuong Viet Nguyen (Global Labor Organization (GLO), 2024)
Very few studies have examined the impacts of both climate change and air pollution on student education outcomes, particularly in a developing country setting. Analyzing a rich database consisting of household and school surveys, test scores, and temperature and air pollution data over the past decade for Viet Nam, we find that a 1 μg/m3 increase in PM2.5 concentration in the month preceding exams leads to 0.015 and 0.010 standard deviation decreases in math and reading scores, respectively. We also find some indicative evidence of stronger impacts of air pollution for younger, primary school students who reside in urban areas and in districts with higher temperatures. While we find some mixed effects of temperature, we do not find significant effects on students' test scores for temperature extremes and air pollution over the past 12 months. Our findings offer policy-relevant inputs for the country's ongoing efforts to fight air pollution.
Keywords: O12; I10; Q53; Q54; 330; air pollution; climate change; weather extremes; education; Viet Nam